2008
DOI: 10.1001/archsurg.143.12.1198
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Esophagectomy as Treatment for Resectable Esophageal Cancer

Abstract: Main Outcome Measures: The rate of surgical intervention was compared across varying patient characteristics, including age, race, comorbidity score, sex, tumor stage, and socioeconomic region. Survival was compared between patients who received surgery and those who did not using Kaplan-Meier curves, the logrank test, and Cox proportional hazards regression. Statistical analysis was performed using the 2 test and multiple logistic regression. Results: The overall rate of surgical intervention in this cohort w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 40 publications
7
62
1
Order By: Relevance
“…Separate analyses of the SEER and SEER-Medicare databases, have shown that surgery is underutilized among black patients with potentially resectable esophageal cancer. [510] The current study confirms that resection rates are lower among non-white patients. It is plausible that disparities in resection rates are more pronounced in black and hispanic patients because of the higher proportion of SCC and therefore mid-esophageal tumors among these groups.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Separate analyses of the SEER and SEER-Medicare databases, have shown that surgery is underutilized among black patients with potentially resectable esophageal cancer. [510] The current study confirms that resection rates are lower among non-white patients. It is plausible that disparities in resection rates are more pronounced in black and hispanic patients because of the higher proportion of SCC and therefore mid-esophageal tumors among these groups.…”
Section: Discussionsupporting
confidence: 80%
“…[79] For many cancer types, race and ethnicity are significant predictors of non-operative management among patients with potentially resectable tumors. [7,1012] Lower socioeconomic status, higher burden of comorbid conditions, and differential access to surgical specialists have been associated with failure to undergo cancer-directed surgery. [13] However, accounting for patient level factors and access-related issues have failed to fully explain the underuse of surgical resection and the excess mortality observed in non-white patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is highly lethal with 11,650 (88.7%) estimated deaths among men and 2,850 (81.2%) among women. 2 Taken together with previous population studies, [3][4][5][6][7][8][9] the latter suggests a survival benefit for women when compared with men. The prevalence of the two main histologic subtypes-adenocarcinoma and squamous cell carcinoma-differs depending on geographic location.…”
Section: Introductionsupporting
confidence: 55%
“…11 In separate studies of the SEER-Medicare database, Paulson et al and Steyerberg et al demonstrated that black patients with early stage esophageal cancer were substantially less likely to undergo surgery compared to whites. 24,25 Mathur and colleagues documented similar findings in patients with early stage liver cancer. 6 …”
Section: Discussionmentioning
confidence: 71%